The incidence of clinically diagnosed chronic obstructive pulmonary disease in patients with spondyloarthritis compared to matched population-based references: a register-based study - Sofia Exarchou; Ankita Sharma; Petros Zamout; Carl Turesson (Clinical Rheumatology, 2026)
Abstract Introduction/Objective To estimate and compare the incidence of chronic obstructive pulmonary disease (COPD) in patients with spondyloarthritis (SpA) to matched population-based references. Methods Patients with ≥ 1 SpA-diagnosis from an outpatient department of rheumatology/internal medicine (≥ 17 years at diagnosis) between January 1, 2000, and June 30, 2005, were identified in a regional healthcare register. From the same register, five controls without SpA-diagnosis were matched to each SpA-case on age at the first ever SpA-diagnosis for the case, municipality of residence at this time, and sex. SpA-cases and controls were followed from Jan 1, 2006, until first occurrence of either COPD (diagnosed in primary or secondary inpatient/outpatient care), rheumatoid arthritis diagnosis, moving from the region, death, or Dec 31, 2018. The incidence rates of COPD in SpA-cases and controls, overall and by age-groups and sex, and the corresponding incidence rate ratios, were estimated. Results A total of 1083/4950 SpA-cases and controls were followed in the present study for 11,790.9/58,876.4 person-years, with 38/220 incident COPD-cases respectively. The estimated incidence of COPD in SpA-cases was 3.22 (95% CI 2.28–4.42) per 1000 person-years, with an incidence rate ratio compared to controls of 0.86 (95% CI 0.59–1.22). Similarly, there were no significant differences in the incidence of COPD in patients with SpA compared to controls in any age group and in both sexes. Conclusions In this register-based cohort study the incidence of COPD in patients with SpA was similar to that in matched population-based references, overall and after stratification for sex and age-groups. Key Points • Spondyloarthritis (SpA) has been associated with comorbidities, e.g. cardiovascular disease. However, evidence regarding the relation between SpA and chronic obstructive pulmonary disease (COPD) is limited. • To our knowledge, this is the first study to investigate the incidence of COPD in a population-based cohort of patients with SpA in general and compare it to the background population. • Using a regional register of primary and specialized care, we found no difference in COPD incidence between those diagnosed with SpA and matched population-based references, overall and after stratification for sex and age group. • The results of the present study suggest that there may not be an association between SpA and COPD. However, further studies in other countries and settings are needed.